2023
DOI: 10.1093/neuonc/noad073.093
|View full text |Cite
|
Sign up to set email alerts
|

Dipg-46. Targeting the Metabolic Erk5-Pfkfb3 Axis in Pediatric Diffuse Midline Glioma

Abstract: Diffuse midline glioma is an aggressive brain tumor with a median age at diagnosis of 6.3 years and 5-year survival rate of 2.2%.The defining histone mutation H3K27M precludes docking of a protein responsible for epigenetic modification resulting in erroneously accessible chromatin and subsequent transcription of oncogenic pathways, including the RAS-MERK5-ERK5 signaling cascade. To determine which oncogenic processes are regulated by extracellular signal-regulated kinase 5 (ERK5), gene-set enrichment analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Some studies have provided evidence of a relationship between ERK5 and cell metabolism. A recent study demonstrated that in diffuse midline glioma, ERK5 regulates the proglycolytic isoenzyme 6-phosphofructo-2-kinase/fructose-2,6-biphosphatase 3 (PFKFB3) via the activation of transcriptional factor MEF2A [ 38 ]. PFKFB3 is involved in the production of fructose-2,6-bisphosphate (F-2,6-BP), a strong activator of 6-phosphofructo-1-kinase (PFK-1), a key regulator of glycolysis.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have provided evidence of a relationship between ERK5 and cell metabolism. A recent study demonstrated that in diffuse midline glioma, ERK5 regulates the proglycolytic isoenzyme 6-phosphofructo-2-kinase/fructose-2,6-biphosphatase 3 (PFKFB3) via the activation of transcriptional factor MEF2A [ 38 ]. PFKFB3 is involved in the production of fructose-2,6-bisphosphate (F-2,6-BP), a strong activator of 6-phosphofructo-1-kinase (PFK-1), a key regulator of glycolysis.…”
Section: Discussionmentioning
confidence: 99%